THE EFFECT OF TAXPAYER AWARENESS, QUALITY OF SERVICE, AND TAX PENALTIES ON TAXPAYER COMPLIANCE AT SAMSAT BERSAMA OFFICE IN THE EAST JAKARTA - Rizkiani, Nurfathir (International Journal of Multidisciplinary Research and Literature, 2022)
This study aims to analyze the effect of taxpayer awareness, service quality, and tax sanctions on taxpayer compliance in paying motor vehicle taxes at the SAMSAT Joint Office of East Jakarta City. The method used in this study is quantitative. The sampling technique is Convenience Sampling. The data analysis technique used is multiple regression analysis. The data collection is done by distributing questionnaires. The results of this study are: 1) taxpayer awareness has a positive and significant effect on mandatory compliance. 2) service quality has a positive and significant effect on mandatory compliance. 3) tax sanctions do not affect taxpayer compliance. 4) Simultaneously, taxpayer awareness, service quality, and tax sanctions positively and significantly affect taxpayer compliance. The value of R square obtained is 0.422, meaning that taxpayer awareness, service quality, and tax sanctions affect 42.2% of taxpayer compliance in paying motor vehicle taxes. In comparison, the remaining 57.8% is influenced by other variables not examined in this study